Unhealthy diet in association with abdominal obesity as risk factors for cardiovascular disease: data from the ESSE-RF2 study in the Omsk region - I. A. Viktorova; M. V. Moiseeva; V. L. Stasenko; N. G. Shirlina; M. A. Livzan (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To compare dietary patterns of the Omsk region male and female representatives with and without abdominal obesity (AO).Material and methods. Wthin the second study of Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF2) using a representative sample of Omsk region population aged 25-64 years (n=1648), dietary habits, including 21 food groups, were assessed by the questionnaire method. Eating habits of Omsk region representatives with (n=936) and without AO (n=712) were compared.Results. Insufficient consumption of vegetables and fruits practically does not differ in those with or without AO. Depending on sex, insufficient fruit consumption is more typical for both men and women without AO. In addition, there is insignificant increase of fruit consumption in AO people, especially women (p=0,09). Both men (p=0,05) and women (p=0,045) are less likely to consume meat daily but more often consume fish weekly compared to those without AO. This mainly applies to women, because women with AO, in contrast to those without AO, are significantly less likely to consume insufficient amount of fish (p=0,0001). Compared to women with, men with AO significantly more often daily and weekly consume seafood (p=0,001). Daily milk consumption is much less common in individuals with AO, but only at the expense of men with AO (p=0,0001). Kefir and yogurt, on the contrary, are more often consumed in patients with AO both daily and weekly. Omsk people with AO are less likely to introduce yogurt into their daily diet, mainly at the expense of women with AO (p=0,02). Excessive consumption of pasta is more typical for persons without AO (p=0,0001), and by means of men (p=0,001). Omsk residents with AO more often exclude the sweets and confectionery from diet. In the daily diet, they are much less common in individuals with AO (p=0,0001), especially in men with AO (p=0,0001). The respondents with AO daily consume pickles 1,4 times more often compared with those without AO, and mainly by means of men (p=0,03).Conclusion. Presence of AO somewhat changed the dietary habits of Omsk residents. AO patients are less likely to consume pasta, sweets and confectionery products, but more likely to eat pickles and to add more salt to cooked food, which requires targeted preventive measures, taking into account the identified sex priorities, depending on AO presence.